2002
DOI: 10.1074/jbc.m110009200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Lowers Alzheimer β-Amyloid Generation by Stimulating trans-Golgi Network Vesicle Biogenesis

Abstract: Estrogen reduces the risk of Alzheimer's disease in post-menopausal women, ␤-amyloid (A␤) burden in animal models of Alzheimer's disease, and secretion of A␤ from neuronal cultures. The biological basis for these effects remains unknown. Here, utilizing cell-free systems derived from both neuroblastoma cells and primary neurons, we demonstrate that 17␤-estradiol (17␤-E2) stimulates formation of vesicles containing the ␤-amyloid precursor protein (␤APP) from the transGolgi network (TGN). Accelerated ␤APP traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 44 publications
3
84
0
Order By: Relevance
“…Although the neuroprotective properties of beta-estradiol [51] have been already reported in different diseases and models [52,53], and estrogen effects on neuronal viability have been demonstrated both in vitro and in in vivo [54,55], the underlying molecular mechanisms are still elusive. Our data indicate that beta-estradiol treatment is neuroprotective since it results in increased cell survival and proliferation, accompanied by reduction of ubiquitinated protein inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the neuroprotective properties of beta-estradiol [51] have been already reported in different diseases and models [52,53], and estrogen effects on neuronal viability have been demonstrated both in vitro and in in vivo [54,55], the underlying molecular mechanisms are still elusive. Our data indicate that beta-estradiol treatment is neuroprotective since it results in increased cell survival and proliferation, accompanied by reduction of ubiquitinated protein inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…It has outstanding neuroprotective and neurotrophic activities and has been linked to neurodegenerative diseases, including Alzheimer's disease (AD) [1,2] . A large body of work has shown that estrogen can block β-amyloid peptide (Aβ)-induced neuronal cell death and influence Aβ secretion [3][4][5][6][7] . However, long-term compliance with estrogen administration is estimated to be no more than 15%-40% because of undesirable side effects [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Liquiritigenin (7,4'-dihydroxyflavanone, Figure 1) is a flavonoid extracted from Glycyrrhizae radix that exhibits lifeenhancing properties and is frequently used in traditional Oriental medicine to treat injury or swelling and for detoxification. Our interest in liquiritigenin developed as a result of the following observations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support this notion that estrogen treatment profoundly decreased the levels of amyloid precursor protein by enhancing the degradation of this precursor through the -and -secretase pathways (Amtul et al, 2010). Alternatively, estrogen may reduce available amyloid precursor protein by stimulating the formation of vesicles that uptake this precursor-protein, thereby precluding maximal generation of Amyloid (Greenfield et al, 2002). These findings suggest another mechanism underlying estrogen's protection against Alzheimer's disease involving Amyloid degredation (Liang et al, 2010).…”
Section: Amyloid βmentioning
confidence: 92%
“…In diverse animal models of Alzheimer's disease, estrogen has prevented or delayed the development of Alzheimer's disease pathology in particular Amyloid accumulation and plaque formation (Carroll et al, 2007;Zheng et al, 2002). Mechanistically, estrogen may regulate the production of Amyloid and in turn, sustain an improved Amyloid homeostasis by increasing the metabolism of amyloid precursor protein and destabilization of Amyloid fibrils (Greenfield et al, 2002;Morinaga et al, 2007). Estrogen's bioenergetic protection may also influence Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%